Rice Cultivars Under Salt Stress Show Differential Expression of Genes Related to the Regulation of Na+/K+ Balance - Farooq, Muhammad; Park, Jae-Ryoung; Jang, Yoon-Hee; Kim, Eun-Gyeong; Kim, Kyung-Min (Frontiers in Plant Science, 2021)
Abstract Soil salinity is a major problem in agriculture because high accumulation of Na+ ions in plants causes toxicity that can result in yield reduction. Na+/K+ homeostasis is known to be important for salt tolerance in plants. Na+/K+ homeostasis in rice (Oryza sativa L.) involves nine high-affinity K+ transporter (HKT) encoding Na+-K+ symporter, five OsNHX Na+/H+ antiporters, and OsSOS1 Na+/K+ antiporter genes. In the present study, we investigated various molecular and physiological processes to evaluate germination rate, growth pattern, ion content, and expression of OsHKT, OsNHX, and OsSOS1genes related to Na+/K+ homeostasis in different rice genotypes under salt stress. We found a significant increase in the germination percentage, plant vigor, Na+/K+ ratio, and gene expression of the OsHKT family in both the roots and shoots of the Nagdong cultivar and salt-tolerant cultivar Pokkali. In the roots of Cheongcheong and IR28 cultivars, Na+ ion concentrations were found to be higher than K+ ion concentrations. Similarly, high expression levels of OsHKT1, OsHKT3, and OsHKT6 were observed in Cheongcheong, whereas expression levels of OsHKT9 was high in IR28. The expression patterns of OsNHX and OsSOS1 and regulation of other micronutrients differed in the roots and shoots regions of rice and were generally increased by salt stress. The OsNHX family was also expressed at high levels in the roots of Nagdong and in the roots and shoots of Pokkali; in contrast, comparatively low expression levels were observed in the roots and shoots of Cheongcheong and IR28 (with the exception of high OsNHX1 expression in the roots of IR28). Furthermore, the OsSOS1 gene was highly expressed in the roots of Nagdong and shoots of Cheongcheong. We also observed that salt stress decreases chlorophyll content in IR28 and Pokkali but not in Cheongcheong and Nagdong. This study suggests that under salt stress, cultivar Nagdong has more salt-tolerance than cultivar Cheongcheong.